2023
DOI: 10.1039/d3ew00138e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of membrane fouling in a microalgal-bacterial membrane photobioreactor treating secondary wastewater effluent: effect of photoperiod conditions

Abstract: Microalgal-bacterial membrane photobioreactors (MPBRs) have emerged as a transformative wastewater treatment technology for reducing carbon emissions whilst achieving high quality effluent. However, membrane fouling negatively affects process performance by increasing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…E. Segredo-Morales et al observed the effect of photoperiod on the efficacy of a membrane bioreactor (MBR), specifically membrane fouling. 342 Excellent amounts of biomass concentration (3.21 ± 0.45 g L −1 ) and nutrient elimination rates (4.71 mg N L −1 d −1 and 0.67 mg P L −1 d −1 , respectively) were attained under a moderate photoperiod of 16/8 h.…”
Section: Biofouling and Leaching Issuesmentioning
confidence: 92%
“…E. Segredo-Morales et al observed the effect of photoperiod on the efficacy of a membrane bioreactor (MBR), specifically membrane fouling. 342 Excellent amounts of biomass concentration (3.21 ± 0.45 g L −1 ) and nutrient elimination rates (4.71 mg N L −1 d −1 and 0.67 mg P L −1 d −1 , respectively) were attained under a moderate photoperiod of 16/8 h.…”
Section: Biofouling and Leaching Issuesmentioning
confidence: 92%